A novel IgG-Fc-Fused multiepitope vaccine against Brucella: robust immunogenicity - Aodi Wu; Yuting Zhang; Caidong Liu; Kaiat Zhumanov; Tao He; Kexin Yan; Honghuan Li; Shuangshaung Fu; Xin Li; Wenxiang Zhang; Chuang Meng; Changsuo Zhang; et al. (Microbial Cell Factories)
Abstract Brucellosis is one of the most common zoonotic diseases caused by Brucella spp. However, there is currently no Brucella vaccine available for humans. Although some attenuated live vaccines have been approved for animals, their protective efficacy is suboptimal. In previous studies, we utilized an epitope- and structure-based vaccinology platform to identify the immunodominant epitopes of Brucella antigens OMP19, OMP16, OMP25, and L7/L12, and constructed the multi-epitope vaccine MEV-Fc against Brucella. In this study, OMP19, OMP16, OMP25, and L7/L12, and MEV-Fc was expressed and purified via an Escherichia coli expression system, which validated that MEV-Fc possesses high immunological efficacy and exerts a significant protective effect in BALB/c mice within the Brucella infection model. MEV-Fc enhanced Th1 and Th2 immune responses and strongly induced the production of the pro-inflammatory cytokine IFN-γ. Furthermore, MEV-Fc protected mice against Brucella infection compared to control group (PBS). In conclusion, our results provide new insights and data support for the development of human Brucella vaccines.